Avian Intestinal Mucus Modulates Campylobacter jejuni Gene Expression in a Host-Specific Manner - Looft, Torey; Cai, Guohong; Choudhury, Biswa; Lai, Lisa X.; Lippolis, John D.; Reinhardt, Timothy A.; Sylte, Matthew J.; Casey, Thomas A. (Frontiers in Microbiology, 2019)
Campylobacter jejuni is a leading cause of bacterial foodborne illness in humans worldwide. However, C. jejuni naturally colonizes poultry without causing pathology where it resides deep within mucus of the cecal crypts. Mucus may modulate the pathogenicity of C. jejuni in a species-specific manner, where it is pathogenic in humans and asymptomatic in poultry. Little is known about how intestinal mucus from different host species affects C. jejuni gene expression. In this study we characterized the growth and transcriptome of C. jejuni NCTC11168 cultured in defined media supplemented with or without mucus isolated from avian (chicken or turkey) or mammalian (cow, pig, or sheep) sources. C. jejuni showed substantially improved growth over defined media, with mucus from all species, showing that intestinal mucus was an energy source for C. jejuni. We identified 241 differentially expressed genes from C. jejuni cultured in the presence of mucus after analyzing data across species, compared to defined media. Fucose transporter genes were increased regardless of the source of mucus. Seventy-three genes were differentially expressed when C. jejuni was cultured in avian vs. mammalian mucus. Genes associated with iron acquisition and resistance to oxidative stress were significantly increased in avian mucus. Many of the differentially expressed genes were flanked by differentially expressed antisense RNA asRNA, suggesting a role in gene regulation. This study highlights the interactions between C. jejuni and host mucus and the impact on gene expression, growth and invasion of host cells, suggesting important responses to environmental cues that facilitate intestinal colonization.